Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1128/mbio.01090-23
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of SARS-CoV-2 replication by receptor transporter protein 4 (RTP4)

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is subject to restriction by several interferon-inducible host proteins. To identify novel factors that limit replication of the virus, we tested a panel of genes that we found were induced by interferon treatment of primary human monocytes by RNA sequencing. Further analysis showed that one of the several candidates genes tested, receptor transporter protein 4 (RTP4), that had previously been shown to restrict flavivirus replication, prevented the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…To provide a thorough perspective on human genes that impact SARS-CoV-2 infection and to place our arrayed CRISPR KO screen results within the context of existing research, we have compiled a table that includes findings from a selection of 67 large-scale ‘omic’ studies related to SARS-CoV-2. This compilation encompasses this study and 25 other functional genetic screens for genes that influence SARS-CoV-2 infection [1012, 14, 17, 18, 26, 29, 6076], 24 human genetic studies that correlate certain alleles with severe COVID-19 outcomes [4, 5, 7, 23, 24, 7795], ten publications detailing SARS-CoV-2 protein interactomes [96–105], six focusing on SARS-CoV-2 RNA interactomes [106111], and one that examines proteins with altered phosphorylation states in SARS-CoV-2-infected cells [112] (Supp Tables 9-10 for the full, and summary tables, respectively) . This table highlights the depth of research in publications addressing SARS-CoV-2 infection: genes reported in several independent large-scale studies are more credible candidates for biological relevance ( Supp Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To provide a thorough perspective on human genes that impact SARS-CoV-2 infection and to place our arrayed CRISPR KO screen results within the context of existing research, we have compiled a table that includes findings from a selection of 67 large-scale ‘omic’ studies related to SARS-CoV-2. This compilation encompasses this study and 25 other functional genetic screens for genes that influence SARS-CoV-2 infection [1012, 14, 17, 18, 26, 29, 6076], 24 human genetic studies that correlate certain alleles with severe COVID-19 outcomes [4, 5, 7, 23, 24, 7795], ten publications detailing SARS-CoV-2 protein interactomes [96–105], six focusing on SARS-CoV-2 RNA interactomes [106111], and one that examines proteins with altered phosphorylation states in SARS-CoV-2-infected cells [112] (Supp Tables 9-10 for the full, and summary tables, respectively) . This table highlights the depth of research in publications addressing SARS-CoV-2 infection: genes reported in several independent large-scale studies are more credible candidates for biological relevance ( Supp Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several PLSCR1 variants were enriched in a GWAS on severe COVID-19, with a relatively low odds ratio of approximately 1.2 [23, 24]. Considering the complex redundancies within antiviral defenses, from innate immunity featuring multiple effector ISGs that restrict SARS-CoV-2 [914, 17, 18], to adaptive immunity [154], the modest odds ratio associated with a single effector ISG not involved in IFN signaling may not be unexpected. However, for these very reasons, the identification of PLSCR1 in the GWAS remains noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations